Risk identification and analysis of private hospital constructions in Turkey - Yılmaz, Esra Gülen. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
Investments of Private hospital projects in Turkey are subject to substantial risks, which may not only emerge from project activities such as design and construction, but also from global issues beyond the control of project parties, such as legal and political risks. Therefore, investors must manage risks effectively and efficiently, in hospital projects, in order to ensure a successful delivery. The aim of this study is to identify the potential risks of private hospital investments in Turkey and, as a case study, in order to examine the impacts of risks in private hospital investments causing schedule slippages and cost overruns with a probabilistic plan. The first part of this study includes identifying potential risks for private health sector investment projects. An investment project is evaluated under 2 main processes, namely project development and project implementation processes, which are further detailed and developed into 5 phases as investment planning, design, resource supplying, construction and commissioning. A risk breakdown structure is developed for classifying the identified risks considering these phases. As a result of broad literature reviews and interviews arranged with project managers, construction supervisors, consultants, investors, hospital directors and with many project engineers that have been associated with hospital projects a risk checklist is established, which contains 110 potential risks for hospital projects in Turkey. Subsequently, a case study is performed on a real hospital project in Turkey, in which risks impacting schedule and cost targets of the project are examined. First deterministic cost and schedule plans are developed. Risk identification, qualitative and quantitative risk analysis steps of risk management processes have been illustrated on this project. The project cost and duration is simulated by Monte Carlo simulation technique. Distribution analysis and sensitivity analysis are performed. Domain risk factors that affect the schedule and cost of the hospital construction project are determined. Finally the probabilistic results are compared with the results of deterministic plans, which show the obvious need for risk management in hospital projects in order to see the potential deviations in schedule and cost performances of the projects and to successfully manage the projects. The results of this research will enable private hospital investors not only to be aware of potential risks, which will allow them to focus more attention on the activities which are more critical in terms project targets , but also to show the need to implement risk analysis process through the use of qualitative and quantitative analysis .
Keywords: Risk management.; Risk assessment.; Hospitals -- Risk management.; Hospital buildings -- Design and construction -- Turkey.